Damage assessment of prefabricated prestressed channel slab under plane charge blast. (1st November 2021) - Cai, Runze; Li, Yanzhao; Zhang, Chunxiao; Qi, Hui; Mao, Jize; Pan, Yang; Liu, Hanchao
Highlights: Designed prefabricated prestressed channel slab could resist low-altitude nuclear blast without plastic damage. The plane charge blast test with long positive duration (more than 2 s) was successfully implemented. Positive duration was related to the quality of the overlying soil and the air shock wave overpressure design value. Theoretical calculation and ABAQUS simulation results were verified by experimental data. Abstract: The study of the mechanical properties of prestressed concrete channel slabs under different plane charge air blasts for applications in civil defense engineering is significant. For this reason, similar simulation tests were conducted on the anti-explosive performance of three 1:3 scale prestressed concrete channel slabs under 9 times plane charge air blast. The positive duration was more than 260 ms to simulate the uniform distribution load of a strong blast air shock wave on the prestressed concrete channel slab. The results showed that the designed prestressed concrete channel slab had good displacement ductility without brittle destruction, which significantly reduced the damage of the blasting impact on the structure. The channel slab could resist an air shock load of 0.467 MPa without damage. On the other hand, the positive duration was not only related to the quality of the overlying soil but also related to the air shock wave overpressure design value. The channel plate is regarded as a rigid-plastic component to calculate its plastic dynamic response under explosive load. In addition, the reliability of the theoretical calculation results and ABAQUS software simulation were verified by experimental data, which provided a feasible analytical method for calculation and simulation research in civil air defense engineering.